Felix Tacke, Sprachliche Aufmerksamkeitslenkung. Historische Syntax und Pragmatik romanischer Zeigeaktkonstruktionen, Frankfurt am Main (Vittorio Klostermann) 2022, xiii + 616 p. (Analecta Romanica 92) - Kunert, Irene Dorothea (Vox Romanica)

Präferenzen beim Gebrauch von Konklusionsmarkern im Französischen und im Deutschen - Kunert, Irene Dorothea (Comparatio delectat IV (vorläufiger Titel; Artikel eingereicht 2023))

Nächtliche sympathische Aktivität und subjektive Symptome nach sport-assoziierter Concussion: eine Pilotstudie - Delling, Anne Carina; Jakobsmeyer, Rasmus; Christiansen, Nele; Coenen, Jessica; Reinsberger, Claus (B&G Bewegungstherapie und Gesundheitssport)
Zusammenfassung Einleitung Eine sport-assoziierte Concussion (saC) ist eine oftmals unterschätzte Hirnverletzung, die vor allem in Kontakt- und Kollisionssportarten häufig vorkommt. SaCs können zu einer Vielzahl an klinischen Symptomen führen. Akute und zum Teil die klinische Regeneration überdauernde parasympathische Inhibierung im Autonomen Nervensystem (ANS) wurde nach saC bereits häufig beschrieben. Über Veränderungen im sympathischen Nervensystem ist jedoch noch wenig bekannt. Diese wurden durch Messungen der elektrodermalen Aktivität (EDA) im Schlaf, der erheblich zur Regeneration nach saC beiträgt, sowie im Zusammenhang mit subjektiven Symptomen nach saC im Rahmen einer Pilotstudie untersucht. Methode 18 Sportler und Sportlerinnen mit diagnostizierter saC und 18 nach Alter, Geschlecht, Größe, Gewicht, Sportart und Leistungsklasse gematchte Kontrollathleten und -athletinnen trugen in den Nächten während der individuellen Return-to-Sport (RTS) Phase sowie drei Wochen nach Abschluss des RTS (postRTS) einen Handgelenkssensor (E4 Empatica Inc., Mailand, Italien). Anteile nächtlicher tonischer (meanEDA) und phasischer (EDRs, Schlafstürme) EDA wurden zwecks Gruppenvergleich ermittelt und mit saC-Symptomen (SCAT5) sowie dem subjektiven Erholungszustand nach Schlaf mittels Mann-Whitney U-Tests oder ungepaarten t-Tests verglichen. Ergebnisse Während und nach dem RTS konnten keine Gruppenunterschiede in den nächtlichen EDA-Parametern nachgewiesen werden. Eine höhere meanEDA während des RTS korrelierte mit einer höheren Anzahl an Symptomen (p=0,025, r=0,525) und eine erhöhte phasische EDA mit einem geringeren Anstieg des subjektiven Erholungszustands von vor zu nach Schlaf (EDRs: p=0,007, r=−0,642; EDRs/min: p>0,001, r=−0,762; Schlafstürme: p=0,011, r=−0,616). Fazit Die nächtliche EDA nach saC unterschied sich während und nach dem RTS nicht signifikant zu gematchten Kontrollsportlern und -sportlerinnen. Der Zusammenhang zwischen höherer EDA während des RTS und der Anzahl an saC-Symptomen sowie der geringeren subjektiven Erholung nach Schlaf könnte sowohl ursächlich für als auch Effekt der subjektiven Symptome sein und sollte durch Baseline-Messungen und in Kombination mit parasympathischen Markern künftig weiter untersucht werden.
Keywords: General Medicine

Large Scale Scanning of TLS Session Ticket Confusion - Storm, Tim Leonhard
Session tickets are a resumption mechanism, which can speed up repeated TLS connections. To do so, information is stored client-side, encrypted with an additional symmetric key, which is separate from existing private keys. A server only has to store this key, making session tickets stateless for the server. If the key is shared between servers, a client can be misled into resuming a session with a different, less secure server. In this thesis, we design and implement a scan for detecting prerequisites to such an attack, by requesting and redeeming tickets for pair-wise servers. We find that 17,901 out of 22,127 scanned (virtual) hosts are potentially vulnerable to this attack because they share their keys and accept tickets issued for other domains. We discuss the difficulties of detecting such an attack and show that unfortunately, our approach does not scale to larger sample sizes.

iSAGE: An Incremental Version of SAGE for Online Explanation on Data Streams - Muschalik, Maximilian; Fumagalli, Fabian; Hammer, Barbara; Huellermeier, Eyke (Machine Learning and Knowledge Discovery in Databases: Research Track)

iPDP: On Partial Dependence Plots in Dynamic Modeling Scenarios - Muschalik, Maximilian; Fumagalli, Fabian; Jagtani, Rohit; Hammer, Barbara; Huellermeier, Eyke (Communications in Computer and Information Science)

Rezension zu: Bette, K.-H. & Kühnle, F.: Flitzer im Sport – Zur Sozialfigur des Störenfrieds - Sennefelder, Lisa (Sport und Gesellschaft)

Self-Stabilizing Skip-Graph with Growth-bounded Metric - Beckendorf, Björn

khiṭāb al-karāhiya – iṭlāla ʿala taʾwīlāt maghlūṭa li-n-nuṣūṣ al-islāmiya (Hassrede – Überblick auf kritische Interpretationen islamischer Texte) - Abdelrahem, Mohammed (khiṭāb al-karāhiya wa-taḥaddiyāt al-ḥiwār – taqāṭuʿāt wa-muwāǧahāt (Hassrede und die Herausforderungen des Dialogs – Überschneidungen und Konfrontationen))
Keywords: Dialog der Religionen; interreligiöser Dialog; Hass; Hassrede

Incremental permutation feature importance (iPFI): towards online explanations on data streams - Fumagalli, Fabian; Muschalik, Maximilian; Hüllermeier, Eyke; Hammer, Barbara (Machine Learning)
Abstract Explainable artificial intelligence has mainly focused on static learning scenarios so far. We are interested in dynamic scenarios where data is sampled progressively, and learning is done in an incremental rather than a batch mode. We seek efficient incremental algorithms for computing feature importance (FI). Permutation feature importance (PFI) is a well-established model-agnostic measure to obtain global FI based on feature marginalization of absent features. We propose an efficient, model-agnostic algorithm called iPFI to estimate this measure incrementally and under dynamic modeling conditions including concept drift. We prove theoretical guarantees on the approximation quality in terms of expectation and variance. To validate our theoretical findings and the efficacy of our approaches in incremental scenarios dealing with streaming data rather than traditional batch settings, we conduct multiple experimental studies on benchmark data with and without concept drift.
Keywords: Artificial Intelligence; Software

On Feature Removal for Explainability in Dynamic Environments - Fumagalli, Fabian; Muschalik, Maximilian; Hüllermeier, Eyke; Hammer, Barbara (ESANN 2023 proceedings)

SHAP-IQ: Unified Approximation of any-order Shapley Interactions - Fumagalli, Fabian; Muschalik, Maximilian; Kolpaczki, Patrick; Hüllermeier, Eyke; Hammer, Barbara (NeurIPS 2023 - Advances in Neural Information Processing Systems)

LitCQD: Multi-Hop Reasoning in Incomplete Knowledge Graphs with Numeric Literals - Demir, Caglar; Wiebesiek, Michel; Lu, Renzhong; Ngonga Ngomo, Axel-Cyrille; Heindorf, Stefan (ECML PKDD)

Iron(III)-Complexes with N-Phenylpyrazole-Based Ligands - Hirschhausen, Tanja; Fritsch, Lorena; Lux, Franziska; Steube, Jakob; Schoch, Roland; Neuba, Adam; Egold, Hans; Bauer, Matthias (Inorganics)
The use of iron as a replacement for noble metals in photochemical and photophysical applications is challenging due to the typically fast deactivation of short-lived catalytically active states. Recent success of a cyclometalated iron(III) complex utilizing a bis-tridentate ligand motif inspired the use of phenyl-1H-pyrazole as a bidentate ligand. Five complexes using the tris(1-phenylpyrazolato-N,C2)iron(III) complex scaffold are presented. In addition to the parent complex, four derivatives with functionalization in the meta-position of the phenyl ring are thoroughly investigated by single crystal diffractometry, UV-Vis-spectroscopy, and cyclic voltammetry. Advanced X-ray spectroscopy in the form of X-ray absorption and emission spectroscopy allows unique insights into the electronic structure as well as DFT calculations. The ligand design leads to overlapping MLCT and LMCT absorption bands, and emissive behavior is suppressed by low-lying MC states.
Keywords: Inorganic Chemistry; Computing Resources Provided by the Paderborn Center for Parallel Computing; pc2-ressources

Direct Synthesis of Acetone by Aerobic Propane Oxidation Promoted by Photoactive Iron(III) Chloride under Mild Conditions - Rogolino, Andrea; Filho, José B. G.; Fritsch, Lorena; Ardisson, José D.; da Silva, Marcos A. R.; Atta Diab, Gabriel Ali; Silva, Ingrid Fernandes; Moraes, Carlos André Ferreira; Forim, Moacir Rossi; Bauer, Matthias; Kühne, Thomas D.; Antonietti, Markus; et al. (ACS Catalysis)
Keywords: Catalysis; General Chemistry; pc2-ressources; Computing Resources Provided by the Paderborn Center for Parallel Computing

Electronic Structure and Excited-State Dynamics of the NIR-II Emissive Molybdenum(III) Analogue to the Molecular Ruby - Kitzmann, Winald R.; Hunger, David; Reponen, Antti-Pekka M.; Förster, Christoph; Schoch, Roland; Bauer, Matthias; Feldmann, Sascha; van Slageren, Joris; Heinze, Katja (Inorganic Chemistry)
Photoactive chromium(III) complexes saw a conceptual breakthrough with the discovery of the prototypical molecular ruby mer-[Cr(ddpd)2]3+ (ddpd = N,N′-dimethyl-N,N′-dipyridin-2-ylpyridine-2,6-diamine), which shows intense long-lived near-infrared (NIR) phosphorescence from metal-centered spin-flip states. In contrast to the numerous studies on chromium(III) photophysics, only 10 luminescent molybdenum(III) complexes have been reported so far. Here, we present the synthesis and characterization of mer-MoX3(ddpd) (1, X = Cl; 2, X = Br) and cisfac-[Mo(ddpd)2]3+ (cisfac-[3]3+), an isomeric heavy homologue of the prototypical molecular ruby. For cisfac-[3]3+, we found strong zero-field splitting using magnetic susceptibility measurements and electron paramagnetic resonance spectroscopy. Electronic spectra covering the spin-forbidden transitions show that the spin-flip states in mer-1, mer-2, and cisfac-[3]3+ are much lower in energy than those in comparable chromium(III) compounds. While all three complexes show weak spin-flip phosphorescence in NIR-II, the emission of cisfac-[3]3+ peaking at 1550 nm is particularly low in energy. Femtosecond transient absorption spectroscopy reveals a short excited-state lifetime of 1.4 ns, 6 orders of magnitude shorter than that of mer-[Cr(ddpd)2]3+. Using density functional theory and ab initio multireference calculations, we break down the reasons for this disparity and derive principles for the design of future stable photoactive molybdenum(III) complexes.
Keywords: Inorganic Chemistry; Physical and Theoretical Chemistry

Chemical and photophysical properties of amine functionalized bis‐NHC‐pyridine‐RuII complexes - Fritsch, Lorena; Vukadinovic, Yannik; Lang, Moritz; Naumann, Robert; Bertrams, Maria-Sophie; Kruse, Ayla; Schoch, Roland; Müller, Patrick; Neuba, Adam; Dierks, Philipp; Lochbrunner, Stefan; Kerzig, Christoph; et al. (ChemPhotoChem)
The effects of backbone amine functionalization in three new homoleptic C^N^C type ruthenium(II) complexes bearing a tridentate bis‐imidazole‐2‐ylidene pyridine ligand framework are characterized and studied by single crystal diffraction, electrochemistry, optical spectroscopy and transient absorption spectroscopy in combination with ab initio DFT calculations. Functionalization by dimethylamine groups in 4‐position of the pyridine backbone significantly influences the properties of the complexes as revealed by comparison with the unfunctionalized references. As a result of the amine functionalization, a higher molar absorption coefficient of the MLCT bands, a decreased photoluminescence quantum yield at room temperature together with a shortened excited state lifetime but an improved photostability is observed. Introduction of electron donating and withdrawing groups at the NHC unit modifies the electronic and optical properties, such as the oxidation potential, absorption and emission properties, and the lifetimes of the excited states.
Keywords: Organic Chemistry; Physical and Theoretical Chemistry; Analytical Chemistry; Computing Resources Provided by the Paderborn Center for Parallel Computing; pc2-ressources

The use of IT and OER to support remote sustainable work in Europeans Green Economy - Beutner, Marc; Schneider, Jennifer Nicole (International Conference on Industry Sciences and Computer Science Innovation)

Weiterbildung des Weiterbildungspersonals – Vorwiegend eine Aufgabe des Lernens am Arbeitsplatz - Schwede, Jana; Harteis, Christian (Nachhaltigkeitsorientierte Weiterbildungsdidaktik: Die doppelte Multiplikatorenqualifizierung)

Auswirkungen einer Online-Intervention (Mindset, Lerntechniken) auf den Studieneinstieg - Diederich, Malte; Spatz, Verena; Bauer, Anna Brigitte (Phydid B, Didaktik der Physik, Beiträge zur DPG-Frühjahrstagung (2022))